Extreme Temperatures and Time-Use in China - Teevrat Garg; Matthew Gibson; Fanglin Sun (Institute of Labor Economics (IZA), 2019)
How do people in developing countries respond to extreme temperatures? Using individual-level panel data over two decades and relying on plausibly exogenous variation in weather, we estimate how extreme temperatures affect time use in China. Extreme temperatures reduce time spent working, and this effect is largest for female farmers. Hot days reduce time spent by women on outdoor chores, but we find no such effects for men. Finally, hot days dramatically reduce time spent on childcare, reflecting large effects on home production. Taken together, our results suggest time use is an important margin of response to extreme temperatures.
Keywords: Q54; O13; H53; 330; extreme weather; time use; gender